Self Efficacy Related to Self Management on Diabetes Mellitus Type II - Hosnaini, Hosnaini; Zakiyah Yasin; Nelyta Oktavianisya; Sugesti Aliftitah; Emdat Suprayitno (CV. AFDIFAL MAJU BERKAH, 2024)
Degenerative disease occur frequently to people who has unhealthy life style. Degenerative disease is uncontagious disease, and Diabetes Melitus is one of them.The aim of this study was to know correlation between self efficacy and self management on DM type II patients in puskesmas saronggi area. This study was analytic observational study with correlational approach. Total population in this study were 259. simple random sampling technique had used in this study. And so 72 samples has choosen. Questionnaires has used to measure the correlation between self efficacy and self management. The data analized by Rank Spearman test. The result of the study showed that most of DM type II patients in saronggi have good self efficacy, and almost all respondents have great self management. The result of analizing data about correlation between self efficacy and self management showed p=0,020 (a < 0,05), therefore there was correlation between self efficacy and self management on DM type II patients. Thus self efficacy and self management become patients basic component on conducting diabetic program. Health staff could held accompaniment which can improve patients self efficacy in order to increase their great self management. Accompaniment to improve patients self efficacy may include health promotion and education about how important to improve their self management.